Palladium‐Catalyzed Three‐Component Reaction of 3‐(Tri‐n‐ butylstannyl)allyl Acetates, Aldehydes, and Triorganoboranes: An Alternative to the Carbonyl Allylation Using α, γ‐Substituted Allylic Tin Reagents. Issue 7 (8th March 2016) - Horino, Yoshikazu; Sugata, Miki; Abe, Hitoshi
Abstract: A three‐component reaction of 3‐(tri‐ n ‐butylstannyl)allyl acetates, aldehydes, and triorganoboranes in the presence of a palladium‐Xantphos catalyst system predominately gave ( E )‐ anti ‐homoallylic alcohols with high diastereoselectivity and good to high levels of alkene stereocontrol. An efficient chirality transfer was observed when an enantioenriched substrate was employed. The reaction was initiated by the formation of an allylic gem ‐palladium/stannyl intermediate, which subsequently underwent allylation of the aldehyde by an allyltributyltin followed by a coupling reaction of the in‐situ ‐generated ( E )‐vinylpalladium acetate with the triorganoborane. Abstract :